A review: green chemical mechanical polishing for metals and brittle wafers. (1st July 2021) - Liu, Lu; Zhang, Zhenyu; Wu, Bin; Hu, Wei; Meng, Fanning; Li, Yubiao
Abstract: Chemical mechanical polishing (CMP) is the most effective technique to obtain global and local planarization of metal and brittle surfaces. Conventionally, CMP slurries contain strong acids, alkalis, or hazardous chemicals, which easily cause widespread environmental pollution and are harmful to the operators. It is a challenge to develop a novel green CMP slurry with eco-friendly and non-toxic compositions. Some substances with special structures contain versatile functional groups and have unique physical and chemical properties, including excellent chelating ability, ionization activity, biocompatibility and biodegradability, which have attracted the interest of CMP processing techniques. Therefore, researchers have begun to explore CMP slurries composed of environmentally friendly compositions. This review discussed the latest developments in the field of green CMP of metals and brittle wafers. The research on green CMP slurries was summarized and the future of the field was discussed.